USING FLYSWATTER GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT GRADE EIGTH SMP DWI SEJAHTERA PEKANBARU - Antri Lilin Ima Silaban; Refika Refika (ELT-Lectura, 2017)
At the eight grade of SMP Dwi Sejahtera Pekanbaru, the researcher found some problem, such : they were lack of vocabulary, could not easy to memories the word, express the repitition word, low of motivation, bored of monotoun method, and they were shy to speak. They could not pass the passing grade (78), that’s why the researcher conducted this research aimed to improve students’ vocabulary mastery in short functional text by using flyswatter game. This research was Classroom Action Research (CAR). There were 30 students as participants, the instruments were test, observation, field note, and interview as the instrument. This research consisted of one cycle in which each cycle consisted of five meetings and one test. After conducting this research, it was found that the students’ vocabulary mastery in short functonal text was improved in cycle 1. the average score was 83.67. The improvement was was influence by some factors such the students’ enjoy in everysingle step,using flyswatter game could make the students more active, have some vocabularies, the teacher was explain the material clearly and using madia, and classroom condition very support the activities . It could be concluded that flyswatter game could improve students’ vocabulary mastery in short functional text